ChatGPT as an AI-enabled Academic Assistant: Attitude and Usage among Fisheries Students - Das, Srichandan; Argade, Shivaji Dadabhau; Kumar De, Himansu; Kilodas, Radhakrishnan; Sahoo, Biswajit; Sreenivasan, Periyasamy (Indian Journal of Extension Education, 2024)
Educational landscape stands to undergo a profound transformation with the advent of ChatGPT, an AI-driven academic assistant which empowers students to access information, create content, and enhanced learning experiences. Compared to Google BARD and Bing Chat, ChatGPT emerges as superior choice for text-based content and language-related tasks, offering the potential to streamline academic endeavors and deliver personalized learning experiences. ChatGPT stands out for its versatility in academic settings. The study focused on how fisheries students perceive and utilize ChatGPT within their specialized field, employing a validated Technology Acceptance Model framework. Among 84 participants, mostly post-graduate students averaging 24.5 years of age, findings revealed that 75 per cent had prior knowledge of ChatGPT, and 70 per cent reported using it. Notably, 38 per cent expressed highly favorable attitudes toward its usage. An independent t-test revealed gender differences in ChatGPT usage among fisheries students. Principal Component Analysis highlighted factors influencing ChatGPT adoption, such as innovativeness, perceived risk, anxiety, and academic integrity concerns among non-users, while users were driven by cognitive behavior factors, perceived usefulness, attitude, peer influence, innovativeness, and ease of use. The findings deepen our understanding of AI assistants’ acceptance and usage in academia, setting the stage for further research in this evolving field.
Keywords: ChatGPT; AI-enabled assistant; Attitude; Technology acceptance model; Fisheries students